Strategies for Developing MSMEs Based on the Creative Economy to Enhance Local Community Welfare - Wikansari, Rinandita; Kurniawati, Renny; Prasaja, Disma; Helvianto, Ahmad Wimbo (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to explore strategies for developing MSMEs based on the creative economy to enhance the welfare of local communities. Using a literature review and qualitative approach, the research analyzed 15 scholarly articles retrieved from Google Scholar during the 2016–2024 period. The findings indicate that strategies such as product innovation, digitalization, cross-sector collaboration, and accessible financing significantly impact the competitiveness and sustainability of MSMEs. Case studies from various regions in Indonesia, such as NTT’s woven crafts, Penglipuran Village in Bali, and Yogyakarta's batik industry, provide evidence that creative economy-based approaches not only increase community income but also preserve local cultural values. This research offers practical insights for MSME actors, policymakers, and local communities to strengthen the contribution of MSMEs to sustainable economic and social development.